2017
DOI: 10.1016/j.eurpolymj.2017.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of electrospun alginate nanofibers loaded with ciprofloxacin hydrochloride

Abstract: Alginate nanofibers were prepared in the presence of poly(ethylene oxide) (PEO), a surfactant Pluronic F-127, and a model drug (ciprofloxacin hydrochloride, CpHCl), all mixed prior to electrospinning. It was demonstrated that addition of a carrier polymer (PEO) and a small amount of surfactant are necessary to obtain uniform alginate fibers with cylindrical shape and regular morphology. Importantly, PEO was completely removed from the resulting nanofibers during crosslinking and stabilization post-treatment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…This decline might be due to the degradation of hinokitiol in PBS solution by light, heat, or solvent (ethanol). In the study of ciprofloxacin hydrochloride (CpHCl) release from electrospun alginate [42], at around 24% release of total loaded drug, the cross-linking process between CpHCl molecules in the nanofibers happened and affected the release behaviors. This result also suggests the relation between the release capacity and the characteristics of PHBH, which is hydrophobic polymer.…”
Section: Release Behavior Of Natural Antibacterial Productmentioning
confidence: 99%
“…This decline might be due to the degradation of hinokitiol in PBS solution by light, heat, or solvent (ethanol). In the study of ciprofloxacin hydrochloride (CpHCl) release from electrospun alginate [42], at around 24% release of total loaded drug, the cross-linking process between CpHCl molecules in the nanofibers happened and affected the release behaviors. This result also suggests the relation between the release capacity and the characteristics of PHBH, which is hydrophobic polymer.…”
Section: Release Behavior Of Natural Antibacterial Productmentioning
confidence: 99%
“…The replacement of the co-solvent and surfactant can be achieved by modification of the alginate in order to replace the -OH groups, either via esterification, oxidation, or sulfation [7,21,[42][43][44][45][46]. These processes introduce other functional groups onto the backbone of alginate by replacing the -OH groups, thereby reducing the intra-and inter-molecular hydrogen bonding network, which contributes to the rigidity in chain conformation [18,42].…”
Section: Structural Modificationmentioning
confidence: 99%
“…The obtained macroscopic results Journal of Nanomaterials and histopathological analysis showed that both the colloidal solution and the microfibers had shown statistically equivalent results as the respective commercial products, although the amount of silver applied to the wound was about two orders of magnitude lower. Kyzioł et al [89] prepared alginate nanofibers in the presence of poly(ethylene oxide) (PEO), a surfactant Pluronic F-127, and a model drug (ciprofloxacin hydrochloride, CpHCl), all mixed prior to electrospin. It was demonstrated that the addition of a carrier polymer (PEO) and a small amount of surfactant are necessary to obtain uniform alginate fibers with cylindrical shape and regular morphology.…”
Section: Wound Dressing Applications Of Electrospun Alginatementioning
confidence: 99%